(untitled) (Intent Research Scientific Journal, 2023)
Pedagogical design in the educational process conducted by a pedagogue has become one of the topical topics in recent years due to changes in social and cultural development. Many scientists have given a number of opinions and comments on the organization of pedagogical design processes in education. The design process covers the situation from the beginning to the end of the work in the organization of work, which is considered relevant in each field . Pedagogical designing is of great importance in the organization of the educational process. Explaining using pedagogical designing in the process of education means gaining new knowledge about it.